The study of movement of the wide span tractor-based field machine unit with power method of its control - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Nozdrovicky, L.; Krocko, V.; Findura, P.; Smolinskyi, S.; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; et al. (My University, 2018)
Recently, rapid development of controlled traffi c farming convincingly demonstrates the broad prospects of using the wide span tractor-based fi eld machines throughout the world. The issue at hand lies in the fact that having a wide span tractor-based machine with steering-wheel system moving along the tracks of a constant technological track is not a rational option. According to the concept of bridge and rutting agriculture, it is advisable to subordinate the automated means of mechanization to the principles of the functioning of the coordinate transport system in which machines can move only in two mutually perpendicular directions and for implementation of which the fi eld must have strictly defi ned dimensions. Therefore, a method of power steering similar to a crawler tractor (track-type tractor) can be more effi cient in the automatic driving of bridge means of mechanization within the coordinate-transport system than a kinematic control. Furthermore, methodology utilized for selection of design schemes, parameters and operating modes of machine-tractor aggregates can not be used for study of dynamics of the wide span tractorbased field machine. Theoretical study is based on theoretical mechanics, theory of mobile energy facilities, statistical dynamics and theory of automatic control of linear dynamical systems with reproduction of statistically random control and disturbing input effects. Purpose of the research lies in development of a dynamic model of plane parallel motion in the horizontal plane of a wide span tractor-based fi eld machine unit using a power (onboard) method of control, which would allow investigation of impacts of the control parameters and disturbing infl uences on the controllability and stability of its motion. Mathematical models have been developed and new regularities of the straightforward parallel movement of the wide span tractor-based fi eld machine unit for controlled traffi c farming have been obtained. The results obtained allow the validation of new schemes, design parameters and modes of operation with acceptable controllability and stability of movement in the horizontal plane with a power control method of the chassis.
Keywords: controlled traffi c farming; wide span tractor-based machine; theoretical research; power method of machine motion control